2016
DOI: 10.13080/z-a.2016.103.034
|View full text |Cite
|
Sign up to set email alerts
|

The variation of agronomic traits associated with breeding progress in winter barley cultivars

Abstract: In the 20 th century, grain yield of winter barley has increased due to advances in both breeding and crop management practices. Knowledge about the association of agronomic traits with genetic gains in yield potential is necessary to improve future breeding programs. Therefore, we studied the variation in grain yield, spike length, heading date, thousand grain weight, hectolitre mass and plant height of two-rowed winter barley cultivars that were released between 1977 and 2010, in a 2-year field trial. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
14
1
3
Order By: Relevance
“…In the present study, grain yield of six-rowed winter barley cultivars increased linearly by 0.055 t ha -1 yr -1 at 0N and by 0.061 t ha -1 yr -1 at 100N, indicating that the rate of genetic progress in six-rowed winter barley did not reach plateau in southern Pannonian Plain. Grain yield progress in six-rowed winter barley is slightly higher than that reported by Mirosavljević et al (2016) in two-rowed winter barley, who reported grain yield progress of 0.046 t ha -1 yr -1 for cultivars released in the past 40 years in Serbia. Genetic improvement of winter barley grain yield has been reported to be 0.013 ± 0.003 t ha -1 yr -1 from 1942 and 1988 in Nordic countries (Ortiz et al, 2002) and 0.020 t ha -1 yr -1 from 1944 and 1998 in Argentina (Abeledo et al, 2003).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In the present study, grain yield of six-rowed winter barley cultivars increased linearly by 0.055 t ha -1 yr -1 at 0N and by 0.061 t ha -1 yr -1 at 100N, indicating that the rate of genetic progress in six-rowed winter barley did not reach plateau in southern Pannonian Plain. Grain yield progress in six-rowed winter barley is slightly higher than that reported by Mirosavljević et al (2016) in two-rowed winter barley, who reported grain yield progress of 0.046 t ha -1 yr -1 for cultivars released in the past 40 years in Serbia. Genetic improvement of winter barley grain yield has been reported to be 0.013 ± 0.003 t ha -1 yr -1 from 1942 and 1988 in Nordic countries (Ortiz et al, 2002) and 0.020 t ha -1 yr -1 from 1944 and 1998 in Argentina (Abeledo et al, 2003).…”
Section: Discussioncontrasting
confidence: 64%
“…Studies of grain yield progress in a set of historical cultivars showed an increase in grain yield in different cereal crops, maize (Mitrović et al, 2016), durum wheat (Álvaro et al, 2008) and bread wheat (Sanchez-Garcia et al, 2013), where only few studies analysed genetic progress in winter barley grain yield (Abeledo et al, 2003;Bingham et al, 2012). Moreover, studies on the genetic gains in winter barley breeding were mainly restricted to two-rowed winter barley cultivars (Mirosavljević et al, 2016) or limited to non-Pannonian environments, such as Nordic European countries (Bertholdsson, Kolodinska Brantestam, 2009), the United Kingdom (Bingham et al, 2012) or South America (Abeledo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…previous studies reported absence of significant association between grain weight and grain yield in wheat (Prado et al, 2017) and barley (Mirosavljević et al, 2016). Grain yield improvement in small grain cereal crops was not followed by significant increase in grain weight with year of cultivar release (Acreche et al, 2008).…”
Section: Relationship Among Studied Traitsmentioning
confidence: 72%
“…Several studies on the effect of breeding on pre-anthesis duration reported contrasting results in barley. Although the modern barley varieties had a shorter pre-anthesis period in Italy (Martintello et al 1987), there was no clear breeding effect on the heading date of two-rowed barley cultivars in the Pannonian Plain (Grausgruber et al 2002, Mirosavljević et al 2016, while modern Argentinian barley cultivars tend to have a longer pre-heading period (Abeledo et al 2003). According to previous studies, a significant decrease in pre-anthesis duration has been recorded in bread wheat (Beche et al 2018) and durum wheat (Isidro et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Different rates of genetic improvement were recorded for the main cereal crops on the Pannonian Plain (Mladenov et al 2011, Mirosavljević et al 2016. For barley grain yield potential in the past century (Lillemo et al 2010), the improvement was associated with significant changes in key agronomic (Ortiz et al 2002) and physiological traits (Abeledo et al 2004).…”
Section: Introductionmentioning
confidence: 99%